KATEGORI DAN FUNGSI SOSIAL UNGKAPAN KEPERCAYAAN MASYARAKAT LARANG PANTANG CALON PENGANTIN PEREMPUAN DI NAGARI BARUNG-BARUNG BALANTAI KECAMATAN KOTO XI TARUSAN KABUPATEN PESISIR SELATAN - Sefridanita Sefridanita; Nurizzati Nurizzati; Zulfikarni Zulfikarni (Jurnal Bahasa dan Sastra, 2012)
This study aimed to describe the categories and functions of social expression trust of the bans abstinence bride growing in Nagari Barung-barung Balantai sub-Distric Koto XI Tarusan Distric Pesisir Selatan. The data was done by using the following: (1) determine the informant who meets the criteria of a good informant, (2) conduct interviews, take notes, and record an expression of the confidence of informants, (3) keep records of returning the record that has been done, (4) enter data into a inventory data format. Data were analyzed with the following steps: (1) move recordings into written language, (2) interpretation and describe the recording into Indonesian, (3) classify each expression of the people by category and function, (4) draw conclusions and write a report. The findings of this study concluded that the ban abstinence expression of the bride is a means of communication in the hearts and feelings expressed in figurative language.